Earthquake ethics—Recovering lost ground when disaster strikes. (10th October 2021) - Mahoney, Daniel; Smit, Hunter S.; Wilkinson, Timothy J.
Abstract: Renesas Electronics Corporation is a major global semiconductor supplier headquartered in Japan. It was formed in the early 2000s through the mergers of the semiconductor divisions of Hitachi, Mitsubishi, and NEC Corporation, each of which had a nearly 40‐year history. It is one of the world's leading suppliers of microcontroller devices, the brains of everything electronic and unique to each supplier, such that a redesign of the end‐system is needed to accommodate a change in microcontroller suppliers. Companies representing hundreds of billions of dollars of manufacturing revenue depended on a stable supply of microcontrollers from Renesas. This case‐based research analyzes how an ethical decision‐making framework helped Renesas survive the 2011 Great Japan Earthquake, which damaged Renesas's flagship factory and significantly reduced its production capacity, threatening to roil the global electronics industry. Because of this ethical framework, the company emerged stronger than before after an existential crisis.